Bamboo‐Like Hollow Tubes with MoS2/N‐Doped‐C Interfaces Boost Potassium‐Ion Storage. (13th August 2018) - Jia, Baorui; Yu, Qiyao; Zhao, Yongzhi; Qin, Mingli; Wang, Wei; Liu, Zhiwei; Lao, Cheng‐Yen; Liu, Ye; Wu, Haowang; Zhang, Zili; Qu, Xuanhui
Abstract: Potassium‐ion batteries (KIBs) are new‐concept of low‐cost secondary batteries, but the sluggish kinetics and huge volume expansion during cycling, both rooted in the size of large K ions, lead to poor electrochemical behavior. Here, a bamboo‐like MoS2 /N‐doped‐C hollow tubes are presented with an expanded interlayer distance of 10 Å as a high‐capacity and stable anode material for KIBs. The bamboo‐like structure provides gaps along axial direction in addition to inner cylinder hollow space to mitigate the strains in both radial and vertical directions that ultimately leads to a high structural integrity for stable long‐term cycling. Apart from being a constituent of the interstratified structure the N‐doped‐C layers weave a cage to hold the potassiation products (polysulfide and the Mo nanoparticles) together, thereby effectively hindering the continuing growth of solid electrolyte interphase in the interior of particles. The density functional theory calculations prove that the MoS2 /N‐doped‐C atomic interface can provide an additional attraction toward potassium ion. As a result, it delivers a high capacity at a low current density (330 mAh g −1 at 50 mA g −1 after 50 cycles) and a high‐capacity retention at a high current density (151 mAh g −1 at 500 mA g −1 after 1000 cycles). Abstract : Bamboo‐like hollow tubes with MoS2 /N‐doped‐C interfaces are synthesized as a high‐capacity and stable anode material for potassium‐ion batteries. The superior performance is owing to the bamboo‐like hollow structure, N‐doped‐C‐layers cage, and MoS2 /N‐doped‐C atomic interface.